Long sleep duration in elders without dementia increases risk of dementia mortality (NEDICES) - Benito-León, Julián (Neurology, 2014)
OBJECTIVE: To determine in a population-based study whether long sleep duration was associated with increased risk of dementia mortality. METHODS: In this prospective, population-based study of 3,857 people without dementia aged 65 years and older (NEDICES [Neurological Disorders in Central Spain]), participants reported their daily sleep duration. The average daily total sleep duration was grouped into 3 categories: ≤5 hours (short sleepers), 6–8 hours (reference category), and ≥9 hours (long sleepers). Community-dwelling elders were followed for a median of 12.5 years, after which the death certificates of those who died were examined. RESULTS: A total of 1,822 (47.2%) of 3,857 participants died, including 201 (11.0%) deaths among short sleepers, 832 (45.7%) among long sleepers, and 789 (43.3%) among those participants in the reference category. Of 1,822 deceased participants, 92 (5.1%) had a dementia condition reported on the death certificate (49 [53.3%] were long sleepers, 36 [39.1%] reported sleeping between 6 and 8 hours, and 7 [7.6%] were short sleepers). In an unadjusted Cox model, risk of dementia-specific mortality was increased in long sleepers (hazard ratio for dementia mortality in long sleepers = 1.58, p = 0.04) when compared with the reference group. In a Cox model that adjusted for numerous demographic factors and comorbidities, the hazard ratio for dementia mortality in long sleepers was 1.63 (p = 0.03). CONCLUSIONS: Self-reported long sleep duration was associated with 58% increased risk of dementia-specific mortality in this cohort of elders without dementia. Future studies are required to confirm these findings.